Helicobacter pylori cell translocating kinase (CtkA/JHP0940) is pro-apoptotic in mouse macrophages and acts as auto-phosphorylating tyrosine kinase - Tenguria, Shivendra; Ansari, Suhail A.; Khan, Nooruddin; Ranjan, Amit; Devi, Savita; Tegtmeyer, Nicole; Lind, Judith; Backert, Steffen; Ahmed, Niyaz (International Journal of Medical Microbiology, 2014)
The Helicobacter pylori gene JHP0940 has been shown to encode a serine/threonine kinase which can induce cytokines in gastric epithelial cells relevant to chronic gastric inflammation. Here we demonstrate that JHP0940 can be secreted by the bacteria, triggers apoptosis in cultured mouse macrophages and acts as an auto-phosphorylating tyrosine kinase. Recombinant JHP0940 protein was found to decrease the viability of RAW264.7 cells (a mouse macrophage cell line) up to 55% within 24. h of co-incubation. The decreased cellular viability was due to apoptosis, which was confirmed by TUNEL assay and Fas expression analysis by flow-cytometry. Further, we found that caspase-1 and IL-1beta were activated upon treatment with JHP0940. These results point towards possible action through the host inflammasome. Our in vitro studies using tyrosine kinase assays further demonstrated that JHP0940 acts as auto-phosphorylating tyrosine kinase and induces pro-inflammatory cytokines in RAW264.7 cells. Upon exposure with JHP0940, these cells secreted IL-1beta, TNF-alpha and IL-6, in a dose- and time-dependent manner, as detected by ELISA and transcript profiling by q-RT-PCR. The pro-inflammatory, pro-apoptotic and other regulatory responses triggered by JHP0940 lead to the assumption of its possible role in inducing chronic inflammation for enhanced bacterial persistence and escape from host innate immune responses by apoptosis of macrophages.
Created from Fastlane, Scopus look-up
Keywords: Apoptosis; H. pylori; Inflammation; JHP0940; Kinases; Plasticity region